1995
DOI: 10.1366/0003702953964408
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Aluminum Alloys by Laser-Induced Breakdown Spectroscopy and Plasma Characterization

Abstract: Laser-induced breakdown spectroscopy has been applied to perform elemental analysis of aluminum alloy targets. The plasma is generated by focusing a pulsed Nd:YAG laser on the target in air at atmospheric pressure. Such a plasma was characterized in terms of its appearance, emission spectrum, space-integrated excitation temperature, and electron density. The electron density is inferred from the Stark broadening of the profiles of ionized aluminum lines. The temperature is obtained by using Boltzmann plots of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
168
2
4

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 393 publications
(188 citation statements)
references
References 28 publications
14
168
2
4
Order By: Relevance
“…6 for three ablation fluences between 10 and 20 J/cm 2 .A solution containing 1000 ppm of Fe was used for these measurements and the temperature was determined using Boltzmann plots based on a set of nine Fe I lines between 370 and 377 nm. 45 We checked that no self-absorption occurred for these lines by following the procedure described by Miller and Debroy. 46 One observes that for the highest ablation fluence, 19.4 J/cm 2 , the electron temperature varies from 8500 K just 1 ms after the ablation pulse to about 4500 K after 10 ms. As a first estimate, assuming that the Pb excited states follow a Boltzmann distribution, about 30% and 70% of the atoms lie in the ground state for these two temperatures, respectively.…”
Section: C2 Optimal Plasma Conditions For Efficient Lif Operationmentioning
confidence: 99%
“…6 for three ablation fluences between 10 and 20 J/cm 2 .A solution containing 1000 ppm of Fe was used for these measurements and the temperature was determined using Boltzmann plots based on a set of nine Fe I lines between 370 and 377 nm. 45 We checked that no self-absorption occurred for these lines by following the procedure described by Miller and Debroy. 46 One observes that for the highest ablation fluence, 19.4 J/cm 2 , the electron temperature varies from 8500 K just 1 ms after the ablation pulse to about 4500 K after 10 ms. As a first estimate, assuming that the Pb excited states follow a Boltzmann distribution, about 30% and 70% of the atoms lie in the ground state for these two temperatures, respectively.…”
Section: C2 Optimal Plasma Conditions For Efficient Lif Operationmentioning
confidence: 99%
“…9 This has contributed to an increasing interest in LIBS technology as an analytical technique for rapid detection and quantitation of pharmaceutical materials. Several pharmaceutical applications using LIBS include examples such as the determination of pharmaceutical excipients used in the formulations [10][11][12] quantitative analysis of the drug substance (active pharmaceutical ingredient [API]) in solid dosage forms, 13 determination of magnesium stearate distribution in powder blends, 14,15 tablet coating thickness and uniformity determination of enteric-coated tablets for atline measurements, 16 and effects of physical attributes in LIBS measurement. 17 Mowery et al 16 have illustrated the potential use of LIBS for rapid characterization of film coatings in pharmaceutical products.…”
Section: Introductionmentioning
confidence: 99%
“…The Energy Research Company (ERCo) demonstrated this LIBS immersion probe at the Commonwealth Aluminum's foundry [22]. Sabsabi et al [23,24] developed another LIBS immersion probe to analyze molten zinc. In this probe, the laser head is mounted directly on the LIBS probe without an optical fiber.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%